The Principal Pauline Epistles: A Collation of Old Latin Witnesses - Houghton, H.A.G (New Testament Tools, Studies and Documents, 2018)
This collation presents the evidence for the earliest Latin versions of Romans, 1 and 2 Corinthians and Galatians, enabling scholars to examine the development of the biblical text at an important early stage in its history. Readership: Scholars of the New Testament text, the development of Christian theology, the history of the Latin language, translation studies. An important reference work for research institutes and academic libraries.